The Hybrid Tracheoesophageal Puncture Procedure: Indications and Outcomes. (August 2014) - Damrose, Edward J.; Cho, Do-Yeon; Goode, Richard L.
Objectives: This report aimed to describe a novel and efficient method of tracheoesophageal puncture using a hybrid device assembled from 2 commercially available puncture kits; to demonstrate the utility of this technique in the performance of primary and secondary procedures, under general and local anesthesia, with and without flap reconstruction; and to evaluate the efficacy of concurrent puncture and valve placement. Methods: Thirty-four patients who underwent either primary or secondary tracheoesophageal puncture for voice restoration. Charts were reviewed retrospectively for complications, time to first valve change, operative time, and blood loss. Results: Using this novel hybrid device, simultaneous puncture and valve placement was achieved in 34 consecutive patients. There was 1 major complication; blood loss was negligible; and the procedure could be accomplished in all cases. There were no cases of prosthesis failure as a result of the insertion technique. Conclusion: Concurrent tracheoesophageal puncture and voice prosthesis placement is a simple and efficient method of voice restoration in the laryngectomized patient and can be more easily accomplished with a hybrid device assembled from the components of 2 commercially available puncture kits. It can be performed under local as well as general anesthesia. The procedure is adaptable to a variety of clinical situations.